Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

Near-term extrauterine pregnancy secondary to uterine rupture in a mare - V Palmieri; G Catone; A Conte; T Di Palma; P Liguori; I Izzo; C Vullo (Journal of Equine Veterinary Science, 2026)

Lowland tropical forests remain a methane sink under warming and long-term hurricane disturbance recovery - Gabriele Larocca Conte; Lucia Zuvela; Rachel Cruz-Pérez; Tatiana Barreto-Vélez; Nibia Becerra-Santillan; Sophia F. Campbell; Hieu P. Chu; Trung Dam; Iana F. Grullón-Penkova; Miriam Kleit; Deyaneira A. Ortiz-Iglesias; Laura C. Rubio-Lebrón; et al. (Agricultural and Forest Meteorology, 2026)

Growth modeling of autochthonous molds from the traditional Brazilian dry-cured loin “Socol”: Impact of the abiotic conditions - Denes do Rosario; Juliana X. Bissoli; Pedro H.A. Martins; Brenno A.S. Jacinto; Eniale M. Oliveira; Carlos A. Conte-Junior; Patrícia C. Bernardes (International Journal of Food Microbiology, 2026)

CAR T-cell and oncolytic virus dynamics and determinants of combination therapy success for glioblastoma - Martina Conte; Agata Xella; Ryan T. Woodall; Kevin A. Cassady; Sergio Branciamore; Christine E. Brown; Russell C. Rockne (Mathematical Biosciences, 2025)

Calibration and validation of a dynamic model of the UC San Diego NHERI 6-DOF Large High‐Performance Outdoor Shake Table - C.-T. Lai; J.P. Conte (Engineering Structures, 2025)

A Chromosome Inversion Creates a Supergene for Sex and Colour in Lake Malawi Cichlids - Kristen A. Behrens; Soumya Jailwala; Frances E. Clark; Anne C. Meyer; Nikesh M. Kumar; Adrianus F. Konings; Reade B. Roberts; Matthew A. Conte; Jeffrey T. Streelman; Patrick T. McGrath; Thomas D. Kocher (Molecular Ecology, 2025)
Cichlid fishes have the highest rates of evolutionary turnover of sex chromosomes among vertebrates. Many large structural polymorphisms in the radiation of cichlids in Lake Malawi are associated with sex chromosomes and may also carry adaptive variation. Here, we investigate the structure and evolutionary history of an inversion polymorphism that includes both a ZW sex locus and an orange‐blotch colour polymorphism in the rock‐dwelling cichlid fishes of Lake Malawi. We use long‐read sequencing to characterise the sequence and breakpoints of the inversion. We quantify allele frequency differences across the inversion in population samples of the genera Metriaclima and Labeotropheus . We also examine expression differences of genes in the inversion. The simple inversion spans 7 Mb and is flanked by CACTA transposons that may have catalysed the rearrangement. The region includes ~600 genes, several of which show large differences in expression. Some of these genes are candidates for the sex and colour phenotypes. This inversion is an accessible model system for studying the role of structural polymorphisms and sex chromosome turnover in the adaptive radiation of cichlids in the lakes of East Africa.

Skeletal muscle alterations in Marfan syndrome: a systematic review - Audrei R. Santos; Rita M. S. Gutierrez; Tatiana E. Koike; Talita C. Conte; Caroline C. Real; Nicolas A. Dumont; Elen H. Miyabara (Journal of Muscle Research and Cell Motility, 2025)

Pumpkin seed protein as a carrier for Astaxanthin: Molecular characterization of interactions and implications for stability - Carini A. Lelis; Jelmir C. Andrade; Rayssa C. Lima; Renan A.P. Ribeiro; Ana Flávia C. Pacheco; Flaviana C. Pacheco; Bruno R.C. Leite-Junior; Paulo Henrique C. Paiva; Thiago S. Álvares; Carlos A. Conte-Junior (Food Chemistry, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

Genetic variants and phenotypic data curated for the CAGI6 intellectual disability panel challenge - Maria Cristina Aspromonte; Alessio Del Conte; Roberta Polli; Demetrio Baldo; Francesco Benedicenti; Elisa Bettella; Stefania Bigoni; Stefania Boni; Claudia Ciaccio; Stefano D’Arrigo; Ilaria Donati; Elisa Granocchio; et al. (Human Genetics, 2025)
Neurodevelopmental disorders (NDDs) are common conditions including clinically diverse and genetically heterogeneous diseases, such as intellectual disability, autism spectrum disorders, and epilepsy. The intricate genetic underpinnings of NDDs pose a formidable challenge, given their multifaceted genetic architecture and heterogeneous clinical presentations. This work delves into the intricate interplay between genetic variants and phenotypic manifestations in neurodevelopmental disorders, presenting a dataset curated for the Critical Assessment of Genome Interpretation (CAGI6) ID Panel Challenge. The CAGI6 competition serves as a platform for evaluating the efficacy of computational methods in predicting phenotypic outcomes from genetic data. In this study, a targeted gene panel sequencing has been used to investigate the genetic causes of NDDs in a cohort of 415 paediatric patients. We identified 60 pathogenic and 49 likely pathogenic variants in 102 individuals that accounted for 25% of NDD cases in the cohort. The most mutated genes were ANKRD11, MECP2, ARID1B, ASH1L, CHD8, KDM5C, MED12 and PTCHD 1 The majority of pathogenic variants were de novo, with some inherited from mildly affected parents. Loss-of-function variants were the most common type of pathogenic variant. In silico analysis tools were used to assess the potential impact of variants on splicing and structural/functional effects of missense variants. The study highlights the challenges in variant interpretation especially in cases with atypical phenotypic manifestations. Overall, this study provides valuable insights into the genetic causes of NDDs and emphasises the importance of understanding the underlying genetic factors for accurate diagnosis, and intervention development in neurodevelopmental conditions.

CAGI6 ID panel challenge: assessment of phenotype and variant predictions in 415 children with neurodevelopmental disorders (NDDs) - Maria Cristina Aspromonte; Alessio Del Conte; Shaowen Zhu; Wuwei Tan; Yang Shen; Yexian Zhang; Qi Li; Maggie Haitian Wang; Giulia Babbi; Samuele Bovo; Pier Luigi Martelli; Rita Casadio; et al. (Human Genetics, 2025)
The Genetics of Neurodevelopmental Disorders Lab in Padua provided a new intellectual disability (ID) Panel challenge for computational methods to predict patient phenotypes and their causal variants in the context of the Critical Assessment of the Genome Interpretation, 6th edition (CAGI6). Eight research teams submitted a total of 30 models to predict phenotypes based on the sequences of 74 genes (VCF format) in 415 pediatric patients affected by Neurodevelopmental Disorders (NDDs). NDDs are clinically and genetically heterogeneous conditions, with onset in infant age. Here, we assess the ability and accuracy of computational methods to predict comorbid phenotypes based on clinical features described in each patient and their causal variants. We also evaluated predictions for possible genetic causes in patients without a clear genetic diagnosis. Like the previous ID Panel challenge in CAGI5, seven clinical features (ID, ASD, ataxia, epilepsy, microcephaly, macrocephaly, hypotonia), and variants (Pathogenic/Likely Pathogenic, Variants of Uncertain Significance and Risk Factors) were provided. The phenotypic traits and variant data of 150 patients from the CAGI5 ID Panel Challenge were provided as training set for predictors. The CAGI6 challenge confirms CAGI5 results that predicting phenotypes from gene panel data is highly challenging, with AUC values close to random, and no method able to predict relevant variants with both high accuracy and precision. However, a significant improvement is noted for the best method, with recall increasing from 66% to 82%. Several groups also successfully predicted difficult-to-detect variants, emphasizing the importance of variants initially excluded by the Padua NDD Lab.

Hazardous element inertisation in vitrified silicate ceramics: Effect of different matrices - S. Conte; C. Molinari; M. Ardit; L. Mantovani; M. Tribaudino; G. Cruciani; M. Dondi; C. Zanelli (Journal of Hazardous Materials, 2024)

New evidence of the Green Tuff deposits and post-caldera, recent explosive volcanic activity at Pantelleria volcano (Sicily Channel, Italy) recorded in near-vent marine areas - C. Romagnoli; C. Giglio; A.M. Conte; A. Cloke-Hayes; M. Garcia; G. Gasparotto; S. Benetti (Journal of Volcanology and Geothermal Research, 2024)

Feasibility of NIR spectroscopy coupled with chemometrics for classification of Brazilian specialty coffee - Yhan S. Mutz; Denes do Rosario; Diego Galvan; Rosane Freitas Schwan; Patricia C. Bernardes; Carlos A. Conte-Junior (Food Control, 2023)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Lab-made 3D printed electrochemical sensors coupled with chemometrics for Brazilian coffee authentication - Yhan S. Mutz; Denes do Rosario; Luiz R.G. Silva; Diego Galvan; Jéssica S. Stefano; Bruno C. Janegitz; David A. Weitz; Patricia C. Bernardes; Carlos A. Conte-Junior (Food Chemistry, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Nature-based solutions for nutrient pollution control in European agricultural regions: A literature review - A. Rizzo; C. Sarti; A. Nardini; G. Conte; F. Masi; A. Pistocchi (Ecological Engineering, 2023)

Principles and applications of non-thermal technologies and alternative chemical compounds in meat and fish - Denes K. A. Rosario; Bruna L. Rodrigues; Patricia C. Bernardes; Carlos A. Conte-Junior (Critical Reviews in Food Science and Nutrition, 2021)

Shiga Toxin-Producing and Enteroaggregative Escherichia coli in Animal, Foods, and Humans: Pathogenicity Mechanisms, Detection Methods, and Epidemiology - Ana C. C. Paletta; Vinicius S. Castro; Carlos A. Conte-Junior (Current Microbiology, 2020)

Correction to: Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Effect of Restraining the Base of Support on the Other Biomechanical Features in Patients with Cerebellar Ataxia - C. Conte; Mariano Serrao; L. Cuius; A. Ranavolo; S. Conforto; F. Pierelli; L. Padua (The Cerebellum, 2018)

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

Displacement of native Patagonian freshwater silverside populations (Odontesthes hatcheri, Atherinopsidae) by introgressive hybridization with introduced O. bonariensis - Eva C. Rueda; Kerry A. Mullaney; Cecilia Conte-Grand; Evelyn M. Habit; Víctor Cussac; Guillermo Ortí (Biological Invasions, 2017)

Is there an association between prior anti-inflammatory drug exposure and occurrence of peritonsillar abscess (PTA)? A national multicenter prospective observational case–control study - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Tooth agenesis and orofacial clefting: genetic brothers in arms? - M. Phan; F. Conte; K. D. Khandelwal; C. W. Ockeloen; T. Bartzela; T. Kleefstra; H. van Bokhoven; M. Rubini; H. Zhou; C. E. L. Carels (Human Genetics, 2016)

Peritonsillar abscess (PTA): clinical characteristics, microbiology, drug exposures and outcomes of a large multicenter cohort survey of 412 patients hospitalized in 13 French university hospitals - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

Comparative analysis of nutritional compositions of transgenic RNAi-mediated virus-resistant bean (event EMB-PV051-1) with its non-transgenic counterpart - José L. V. Carvalho; Juliana de Oliveira Santos; Carmine Conte; Sidney Pacheco; Elsa O. P. L. Nogueira; Thiago L. P. O. Souza; Josias C. Faria; Francisco J. L. Aragão (Transgenic Research, 2015)

Total Mercury in Carnivorous Fish from Brazilian Southeast - M. S. Ferreira; A. N. Marques; R. O. R. Ribeiro; C. A. Conte; C. S. Carneiro; R. E. Santelli; A. S. Freire; S. C. São Clemente; E. T. Mársico (Bulletin of Environmental Contamination and Toxicology, 2015)

Genetic diversity of the rare and endangered meadow violet ( Viola pumila Chaix) at the southern margin of its range - F. Buldrini; L. Conte; D. Dallai; C. Ferrari (Plant Biosystems, 2013)

Cephalic morphological variation in freshwater silversides Odontesthes hatcheri and Odontesthes bonariensis in Patagonia: introgression and ecological relationships - S. Crichigno; C. Conte‐Grand; M. Battini; V. Cussac (Journal of Fish Biology, 2013)
Based on geometric morphometrics and discriminant analysis, the percentage of silverside Odontesthes hatcheri and Odontesthes bonariensis individuals identified by a taxonomic key and misclassified by discriminant analysis was obtained and a negative correlation between the percentage of misclassified individuals of O. hatcheri and the distance to the nearest hatchery stocking silversides was found, suggesting a genetic introgression. Morphological analyses between species, between populations and within populations pointed to the same anatomical structures, suggesting a nested variation related to environmental cues such as availability of littoral shelter. The dependence between the cephalic morphology of O. hatcheri and body size would be in agreement with the trophic niche shifts of the species. Introgression adds a new threat to the already observed decline of populations of O. hatcheri and suggests that this species deserves particular consideration in terms of conservation guidelines.

Plasmid-mediated fluoroquinolone resistance determinants in Escherichia coli from community uncomplicated urinary tract infection in an area of high prevalence of quinolone resistance - C. Longhi; M. P. Conte; M. Marazzato; V. Iebba; V. Totino; F. Santangelo; C. Gallinelli; L. Pallecchi; E. Riccobono; S. Schippa; A. Comanducci (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Correlation between cortical plasticity, motor learning and BDNF genotype in healthy subjects - P. Li Voti; A. Conte; A. Suppa; E. Iezzi; M. Bologna; M. S. Aniello; G. Defazio; J. C. Rothwell; Alfredo Berardelli (Experimental Brain Research, 2011)

Potential allelopathic activity of Sideritis italica (Miller) Greuter et Burdet essential oil - A. Basile; R. C. Cobianchi; D. Rigano; F. Senatore; M. Bruno; S. Rosselli; B. Conte; S. Sorbo (Plant Biosystems, 2011)

Phenotypic characterization and putative virulence factors of human, animal and environmental isolates of Plesiomonas shigelloides - A. Salerno; I. Čižnár; K. Krovacek; M. Conte; S. Dumontet; C. González-Rey; V. Pasquale (Folia Microbiologica, 2010)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

Effect of microgravity on gene expression in mouse brain - Antonio Frigeri; Dumitru A. Iacobas; Sanda Iacobas; Grazia Paola Nicchia; Jean Francois Desaphy; Diana Conte Camerino; Maria Svelto; David C. Spray (Experimental Brain Research, 2008)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Competence of Swine Oocytes Matured by Three-dimensional Gonadotropin-free Co-culture - E. Munari; A. Asti; C. Colombani; E. Benzoni; M. Faustini; M. L. Torre; A. Riccardi; S. Villani; L. Sesso; U. Conte; D. Vigo (Veterinary Research Communications, 2007)

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - L. Conte; C. Cotti; G. Cristofolini (Plant Biosystems, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Topiramate and cortical excitability in humans: a study with repetitive transcranial magnetic stimulation - M. Inghilleri; F. Gilio; A. Conte; V. Frasca; C. Marini Bettolo; E. Iacovelli; B. Gregori; M. Prencipe; A. Berardelli (Experimental Brain Research, 2006)

Synaptic potentiation induced by rTMS: effect of lidocaine infusion - M. Inghilleri; A. Conte; V. Frasca; F. Gilio; C. Lorenzano; A. Berardelli (Experimental Brain Research, 2005)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)

Detection of ephemeral genetic sub-structure in the narrow endemic Abies nebrodensis (Lojac.) Mattei (Pinaceae) using RAPD markers - L Conte; C Cotti; R Schicchi; FM Raimondo; G Cristofolini (Plant Biosystems, 2004)

Fogging can control Tetranychus urticae on greenhouse cucumbers - C. Duso; F. Chiarini; L. Conte; V. Bonora; L. Dalla Mont; S. Otto (Journal of Pest Science, 2004)

Molecular and carbon isotopic composition of leaf wax in vegetation and aerosols in a northern prairie ecosystem - Maureen H. Conte; John C. Weber; Peter J. Carlson; Lawrence B. Flanagan (Oecologia, 2003)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Spread of electrical activity at cortical level after repetitive magnetic stimulation in normal subjects - Lorenzano C.; Gilio F.; Inghilleri M.; Conte A.; Fofi L.; Manfredi M.; Berardelli A. (Experimental Brain Research, 2002)

Abdominal Waggings and Variation of Their Rate of Occurrence in the Social Wasp, Polistes dominulus Christ. I. Quantitative Analysis - C. Brillet; S. Semenoff Tian-Chansky; Y. Le Conte (Journal of Insect Behavior, 1999)

Chronic Pulmonary Histoplasmosis in a Patient with a Recent History of Tuberculosis and Persistent Round Lung Lesions - M. A. Viviani; T. Masini; D. Conte; C. Trovato; R. Pometta (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Bactericidal effect of pefloxacin and fosfomycin againstPseudomonas aeruginosa in a rabbit endocarditis model with pharmacokinetics of pefloxacin in humans simulated in vivo - D. Bugnon; G. Potel; Y. Q. Xiong; J. Caillon; D. Navas; C. Gras; M. F. Kergueris; P. Le Conte; F. Jehl; D. Baron; H. Drugeon (European Journal of Clinical Microbiology & Infectious Diseases, 1997)